1992
DOI: 10.3758/bf03203471
|View full text |Cite
|
Sign up to set email alerts
|

A technique for rapid, reliable assessment of thermal-pain threshold in humans

Abstract: A simple and reliable method of assessing pain threshold in humans may be useful in a number of research areas, such as in examining acute antinociceptive effects of drugs. We have developed a low-cost, computer-controlled method to reliably assess thermal-pain threshold using radiant heat focused from a slide projector and applied to a small area of skin. An electronic shutter is attached to the projector opening to provide precise onset and offset of heat. A computer keypad allows for subject response at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Previous work has shown that thermal stimulation methods produce reliable behavioral responding (Hardy, Wolff, & Goodell, 1952; Kenshalo, Anton, & Dubner, 1989; Perkins, Grobe, Jennings, Epstein, & Elash, 1992). Lee and Stitzer (1995) further showed the reliability of this particular procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that thermal stimulation methods produce reliable behavioral responding (Hardy, Wolff, & Goodell, 1952; Kenshalo, Anton, & Dubner, 1989; Perkins, Grobe, Jennings, Epstein, & Elash, 1992). Lee and Stitzer (1995) further showed the reliability of this particular procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The present studies compared pain detection of smokers and nonsmokers in response to measured doses of nicotine administered by nasal spray, which was used to standardize nicotine exposure (Perkins et al, 1986; Perkins, Epstein, Stiller, Marks, & Jacob, 1989). Thermal, or radiant heat, pain was used because it appears to produce little adaptation across presentations (Hardy, Wolff, & Goodell, 1952; Kenshalo, Anton, & Dubner, 1989) and, therefore, may be more reliable (Perkins, Grobe, Jennings, Epstein, & Elash, 1992). Pain detection, rather than endurance, was examined because it is less likely to cause tissue damage and may also be less subject to adaptation across frequent, repeated assessments of pain sensitivity before and after acute drug exposure manipulations (Beecher, 1959; Chapman et al, 1985).…”
mentioning
confidence: 99%
“…However, while there is considerable research on the reliability of PPTs, there is little on the reliability of thermal pain thresholds. That which has been conducted has predominantly focused on response to heatinduced pain and utilised Pearson's r as a reliability measure [22,23]. Perkins et al [23], however, found considerable within-subject variability in heat pain thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…That which has been conducted has predominantly focused on response to heatinduced pain and utilised Pearson's r as a reliability measure [22,23]. Perkins et al [23], however, found considerable within-subject variability in heat pain thresholds. Such a result indicates the potential benefit of using ICC and CV in future studies of thermal pain reliability.…”
Section: Introductionmentioning
confidence: 99%